Population Genomics Reveals Incipient Speciation, Introgression, and Adaptation in the African Mona Monkey (Cercopithecus mona). (28th September 2020) - Ayoola, Adeola Oluwakemi; Zhang, Bao-Lin; Meisel, Richard P; Nneji, Lotanna M; Shao, Yong; Morenikeji, Olanrewaju B; Adeola, Adeniyi C; Ng'ang'a, Said I; Ogunjemite, Babafemi G; Okeyoyin, Agboola O; Roos, Christian; Wu, Dong-Dong
Abstract: Guenons (tribe Cercopithecini ) are the most widely distributed nonhuman primate in the tropical forest belt of Africa and show considerable phenotypic, taxonomic, and ecological diversity. However, genomic information for most species within this group is still lacking. Here, we present a high-quality de novo genome (total 2.90 Gb, contig N50 equal to 22.7 Mb) of the mona monkey ( Cercopithecus mona ), together with genome resequencing data of 13 individuals sampled across Nigeria. Our results showed differentiation between populations from East and West of the Niger River ∼84 ka and potential ancient introgression in the East population from other mona group species. The PTPRK, FRAS1, BNC2, and EDN3 genes related to pigmentation displayed signals of introgression in the East population. Genomic scans suggest that immunity genes such as AKT3 and IL13 (possibly involved in simian immunodeficiency virus defense), and G6PD, a gene involved in malaria resistance, are under positive natural selection. Our study gives insights into differentiation, natural selection, and introgression in guenons.